Cellular Plasticity of CD4+ T Cells in the Intestine - Brucklacher-Waldert, Verena; Carr, Edward J.; Linterman, Michelle A.; Veldhoen, Marc (Frontiers in Immunology, 2014)
Barrier sites such as the gastrointestinal tract are in constant contact with the environment which contains both beneficial and harmful components. The immune system at the epithelia must make the distinction between these components to balance tolerance, protection and immunopathology. This is achieved via multifaceted immune recognition, highly organised lymphoid structures and the interaction of many types of immune cells. The adaptive immune response in the gut is orchestrated by CD4+ helper T (Th) cells which are integral to gut immunity. In recent years it has become apparent that the functional identity of these Th cells is not as fixed as initially thought. Plasticity in differentiated T cell subsets has now been firmly established, in both health and disease. The gut, in particular, utilises CD4+ T cell plasticity to mould CD4+ T cell phenotypes to maintain its finely poised balance of tolerance and inflammation and to encourage biodiversity within the enteric microbiome. In this review we will discuss intestinal helper T cell plasticity and our current understanding of its mechanisms, including our growing knowledge of an evolutionarily ancient symbiosis between microbiota and malleable CD4+ T cell effectors.